PENGEMBANGAN MEDIA PEMBELAJARAN CRAFH MY PROFESSION BERBASIS MACROMEDIA FLASH PADA SUBTEMA AKU DAN CITA-CITAKU KELAS IV SD NEGERI SUCI - Vivien Octaviana Devi; Arya Setya Nugroho (JUSEDA, 2020)
This study aims to develop a Macromedia Flash based learning media learners fourth grade Suci Public Elementary Schools.This type of research is research development with 4-D models but researchers used until the third phase namely, the definition (define), design (design), development (develop). Subjects in this study is the fourth grade learners Suci Public Elementary Schools many as 27 students. Data collection techniques and instruments using validation sheet, questionnaire responses of learners, and achievement test.The results of data analysis showed that the development of Macromedia Flash based learning media in accordance with the quality of instructional media, namely: a) the results of the validation study media do validator earned an average percentage of 89.5% can be considered valid, b) practical learning media categorized as validator states with a little revision, c) effective learning media categorized by the acquisition of classical learning completeness 85%, and the percentage of learners' questionnaire responses to macromedia flash media-based learning by 89.19%.